Automatic Irrigation Based on Soil Moisture for Vegetable Crops - Rafael Muñoz-Carpena; Michael D. Dukes (EDIS)
Improving irrigation efficiency can contribute greatly to reducing production costs of vegetables, making the industry more competitive and sustainable. Through proper irrigation, average vegetable yields can be maintained (or increased) while minimizing environmental impacts caused by excess applied water and subsequent agrichemical leaching. Recent technological advances have made soil water sensors available for efficient and automatic operation of irrigation systems. Automatic soil water sensor-based irrigation seeks to maintain a desired soil water range in the root zone that is optimal for plant growth. This document is AE354, one of a series of the Department of Agricultural and Biological Engineering, UF/IFAS Extension. Original publication date June 2005.